2020
DOI: 10.1186/s12889-020-09521-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term exposure to air pollutants and cardiopulmonary mortality rates in South Korea

Abstract: Background The association between long-term exposure to air pollutants, including nitrogen dioxide (NO2), carbon monoxide (CO), sulfur dioxide (SO2), ozone (O3), and particulate matter 10 μm or less in diameter (PM10), and mortality by ischemic heart disease (IHD), cerebrovascular disease (CVD), pneumonia (PN), and chronic lower respiratory disease (CLRD) is unclear. We investigated whether living in an administrative district with heavy air pollution is associated with an increased risk of mortality by the d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 28 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…An increase in ammonia concentration contributes to PM 2.5 formation in the atmosphere [20], and the contribution of ammonia to atmospheric aerosols affects human health, which can lead to increase in the likelihood of hospitalization. Air pollution affects the respiratory and cardiovascular systems of the body and is one of the causes of high mortality in South Korea [21]. The presence of ammonium sulfate and ammonium nitrate in aerosols significantly impacts climatic conditions [22] as these aerosols absorb solar radiation, further heating the atmosphere and contributing to climate change [23].…”
Section: Introductionmentioning
confidence: 99%
“…An increase in ammonia concentration contributes to PM 2.5 formation in the atmosphere [20], and the contribution of ammonia to atmospheric aerosols affects human health, which can lead to increase in the likelihood of hospitalization. Air pollution affects the respiratory and cardiovascular systems of the body and is one of the causes of high mortality in South Korea [21]. The presence of ammonium sulfate and ammonium nitrate in aerosols significantly impacts climatic conditions [22] as these aerosols absorb solar radiation, further heating the atmosphere and contributing to climate change [23].…”
Section: Introductionmentioning
confidence: 99%
“…The cardiovascular influences were also observed after long-term SO 2 exposure. An investigation conducted in South Korea suggested that longterm exposure to a high level of SO 2 was consistently and significantly associated with an increased ischemic heart disease mortality (153).…”
Section: Epidemiological and Clinical Reportsmentioning
confidence: 99%
“…The pathologies recognized in literature as being connected with this type of pollution [9,10,11,12,13,14,15,16,17,18,19,20,21] , are pathologies corresponding to the following ICD-10 3 codes: . I00 to I199 all diseases of the circulatory system in which are found for example ischemic heart diseases, coronary diseases, .…”
Section: T To T3mentioning
confidence: 99%
“…CB169, TEQ-2005, CB187, 2,3,4,7,8 PeCDF, As, 2,3,7,8 TeCDF, crustaceans, VDL, CB149, CB114, CB157, CB20, CB28, Co, CB194, Abundance, PCB indicators18 Without nonetheless exceeding the threshold of a 0.20 probability, except for example when a pollutant is known for having an impact (of the PCB type or others with a value of 0.18)…”
mentioning
confidence: 99%